High minds the Victorians and the birth of modern Britain - Heffer, Simon 1960- (Pegasus Books, 2022)
"An ambitious exploration of the making of the Victorian Age—and the Victorian mind—by a master historian. Britain in the 1840s was a country wracked by poverty, unrest, and uncertainty; there were attempts to assassinate the queen and her prime minister; and the ruling class lived in fear of riot and revolution. By the 1880s it was a confident nation of progress and prosperity, transformed not just by industrialization but by new attitudes to politics, education, women, and the working class. That it should have changed so radically was very largely the work of an astonishingly dynamic and high-minded group of people—politicians and philanthropists, writers and thinkers—who in a matter of decades fundamentally remade the country, its institutions and its mindset, and laid the foundations for modern society. High Minds explores this process of transformation as it traces the evolution of British democracy and shows how early laissez-faire attitudes to the fate of the less fortunate turned into campaigns to improve their lives and prospects. The narrative analyzes the birth of new attitudes in education, religion, and science. And High Minds shows how even such aesthetic issues as taste in architecture collided with broader debates about the direction that the country should take. In the process, Simon Heffer looks at the lives and deeds of major politicians; at the intellectual arguments that raged among writers and thinkers such as Matthew Arnold, Thomas Carlyle, and Samuel Butler; and at the "great projects" of the age, from the Great Exhibition to the Albert Memorial. Drawing heavily on previously unpublished documents, he offers a superbly nuanced portrait into life in an extraordinary era, populated by extraordinary people—and show how the Victorians’ pursuit of perfection gave birth to the modern Britain we know today."--Publisher description
Reprint. Originally published: London : Random House, 2013
Keywords: Geschichte 1837-1901; Kultur; Politik; Gesellschaft; Großbritannien; Great Britain / Civilization / 19th century; Great Britain / Social conditions / 19th century; Great Britain / Social life and customs / 19th century; Great Britain / History / Victoria, 1837-1901; Great Britain / Politics and government / 1837-1901; Grande-Bretagne / Civilisation / 19e siècle; Grande-Bretagne / Conditions sociales / 19e siècle; Grande-Bretagne / Murs et coutumes / 19e siècle; Grande-Bretagne / Histoire / 1837-1901 (Victoria); Grande-Bretagne / Politique et gouvernement / 1837-1901; Civilization; Manners and customs; Politics and government; Social conditions; Great Britain; 1800-1901; History